All-optical pattern matching system of 42 Gbit/s 4-bit BPSK signals and its demonstration for optoelectronic firewall - Qihan ZHANG; Xiaoxue GONG; Rui LI; Xin LI; Shanguo HUANG; Lei GUO (Tongxin xuebao)
To achieve the all-optical pattern matching for optoelectronic firewall which could process high-speed optical signals efficiently, a BPSK all-optical pattern recognition system with the data rate up to 42 Gbit/s was proposed and demonstrated by employing the commercial optical components.First, the input BPSK sequence was converted to a positive and a negative IM signals by adding in-phase and inverse-phase coherent carriers, respectively.Then the converted IM signals were coupled into time delay lines and optical AND logic gates implemented by HNLF to achieve the optical correlation operation.In the end, a high-level optical pulse indicating the pattern matched result was output.The numerical simulation and the experiment results demonstrate that the proposed system can recognize a 4-bit target BPSK sequence from an 8-bit 42 Gbit/s BPSK input sequence, which proves the feasibility of the all-optical pattern matching of BPSK signals and can be applied to high-speed optoelectronic firewall.